Cannabinoid as Potential Aromatase Inhibitor Through Molecular Modeling and Screening for Anti-Cancer Activity: Cannabinoid as Potential Aromatase Inhibitor Through Molecular Modeling - Baroi, Sudipta; Saha, Achintya; Bachar, Ritesh; Bachar, Sitesh C (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Inhibition of aromatase (CYTP450), a key enzyme in the estrogen biosynthesis, could result in regression of estrogen-dependent tumors and even prevent the promotion of breast cancer. The present research has been designed for searching a potent chemical moiety from natural sources to inhibit aromatase enzyme, the overfunctionality of which causes the breast cancer. Cannabis sativa contains a very much promising group of cannabinoids with more than 66 compounds with reported anticancer property and for the search of a target specific potent aromatase inhibitor, 61 cannabinoids from C. sativa were selected. The Structures Data File (SDF) of these ligand molecules were subjected to docking studies at the binding site of aromatase X-ray crystallographic structure based on lower resolution of the protein crystal structure and higher docking accuracy, predicted by calculating the correlation between experimental activities and Glide dock scores and compared with the standard aromatase ligand androstenedione and aromatase inhibitor fadrozole with existing drug for breast cancer treatment. The best docked pose of each ligand was selected on the basis of the highest dock score related to the binding free energies of the internal dataset compounds as compared to their observed activities. Apart from the hydrogen bond formation with the oxygen present on the aromatic ring system, the other parts of the molecules are stabilized by hydrophobic interactions with non-polar amino acid residues (Ile133, Phe134, Phe221, Trp224, Ile305, Ala306, Ala307, Val369, Val370, Leu372, Val373, Met374 and Leu477). From the screening results of the cannabinoid analogs, 21 out of 61 were found to have an acceptable docking score in comparison to the standards, androstenedione and fadrozole. The pharmacokinetic filters like absorption, distribution, metabolism and excretion and toxicity (ADMET) property determination were applied to select drug-like compounds. Among them three compounds were found to reveal the most promising drug like activity, which were cannabidiorcol (CN 17, CBD-C1), cannabitriol (CN 43, CBT) and cannabiripsol (CN 55, CBR). The ani-cancer activity of the target compounds was performed against brine shrimp lethality biassay, where cannabidiorcol exhibited significant LC50 value of 0.348 ±0.002 μg/ml (R² = 0.9853) which is almost similar to vincristine sulfate (LC50 = 0.316±0.003 μg/ml, R² = 0.9882). Compound cannabitriol also showed promisimg cytotoxicity 0.650±0.004 μg/ml (R² = 0.9882) in comparison to the reference standard. But cannabiripsol demostrated relatively weaker activity 12.95±1.234 μg/ml (R²=0.9897). It can be concluded that the lead compounds may be developed as potent aromatase inhibitor performing their further biological evaluation. Dhaka Univ. J. Pharm. Sci. 19(1): 47-58, 2020 (June)